Long‐term individual retention with cenobamate in adults with focal seizures: Pooled data from the clinical development program. Issue 1 (23rd November 2021) - Sander, Josemir W.; Rosenfeld, William E.; Halford, Jonathan J.; Steinhoff, Bernhard J.; Biton, Victor; Toledo, Manuel
Abstract: Objective: We determined retention on open‐label cenobamate therapy in the clinical development program to assess the long‐term efficacy and tolerability of adjunctive cenobamate in individuals with uncontrolled focal seizures. Methods: Data from two randomized, controlled cenobamate studies and one open‐label safety and pharmacokinetic study were pooled. Based on the percentage of participants remaining on treatment, retention rates were estimated using Kaplan‐Meier survival analyses. We performed two additional analyses to assess factors contributing to retention, stratifying a robust data set (through 2 years) by cenobamate modal dose and frequently used concomitant anti‐seizure medications. Cenobamate discontinuations and treatment‐emergent adverse events were summarized. Results: Data from 1844 participants were pooled: 149 from a single‐dose randomized trial, 355 from a multi‐dose randomized trial, and 1340 from an open‐label safety and pharmacokinetic study. Most participants from randomized trials continued in open‐label extensions, and pooled data represent >95% of participants exposed to cenobamate. Baseline characteristics and disease and treatment histories were similar across studies. Median duration of cenobamate exposure was 34 months, with a median modal dose of 200 mg/day. Kaplan‐Meier estimates of cumulative cenobamate retention rates were 80% at 1 year and 72% at 2 years. Once participants reached the maintenance phase, retention rates were consistently high in participants receiving ≥100 mg/day cenobamate, and concomitant anti‐seizure medications did not affect long‐term retention. By 2 years, 535 (29%) had actually discontinued cenobamate; the most common reasons for discontinuation were adverse events (37.6%), withdrawal of consent (21.1%), and other (16.8%). Significance: Treatment retention rates provide a proxy measure for long‐term efficacy, safety, tolerability, and adherence. The consistently high retention rates we found suggest that cenobamate may be an effective and well‐tolerated new treatment option for people with drug‐resistant focal seizures.